The Water Footprint of Kathmandu Metropolitan City - Shrestha, Mohan Bikram; Khadka, Udhab Raj (Journal of Natural History Museum, 2015)
The water footprint is consumption-based indicator of water use. Water footprint is defined as the total volume of both indirect and the direct freshwater used for producing goods and services consumed by individuals or inhabitants of community. There are many studies regarding the direct water use but studies incorporating both direct and indirect water use is deficient. This study tries to estimate total volume of water based on the consumption pattern of different commodities by individuals of Kathmandu Metropolitan city using extended water footprint calculator. The average water footprint of individuals appears to be 1145.52 m3/yr. The indirect and direct water footprint appears to be 1070.82 Mm3/yr and 46.59 Mm3/yr respectively which cumulatively give the total water footprint of Kathmandu Metropolitan City of 1117.40 Mm3/yr. This volume is equal to 2.27 times the annual flow the River Bagmati. The indirect water footprint includes food water footprint of 1055.60 Mm3/yr or 2.14 times the annual flow and industrial water use of 15.22 Mm3/yr or 0.03 times the annual flow while the direct water footprint includes domestic water use of 46.59 Mm3/yr or 0.09 times the annual flow. In food water footprint, cereals consumption shared the highest contribution of 34.82% followed by meat consumption with share of 32.62% in total water footprint. Per capita per day water use of inhabitants appears to be 3138 liters which includes water use in food items of 2965 liters, industrial water use of 43 liters and domestic water use of 131 liters. The per capita per day domestic water use is 90 liters more than supplement of 41 liters by the water operator of Kathmandu Valley. Per capita per day domestic water use is already 5 liters more than expected improvement in water supplement of 126 liters per capita per day in 2025 after accomplishment of Melamchi water project. And, it is expected to increase further observing the rapid urbanization of Kathmandu Metropolitan City. The study showed water footprint of individuals is directly related to food consumption behavior, life style and services used therefore it is necessary to initiate water offsetting measures at individual level and water operator to find environmentally sustainable alternatives along with ongoing water project to fulfill demand. J. Nat. Hist. Mus. Vol. 28, 2014: 73-80